2004
DOI: 10.1530/rep.1.00288
|View full text |Cite
|
Sign up to set email alerts
|

Hoechst 33342 stain and u.v. laser exposure do not induce genotoxic effects in flow-sorted boar spermatozoa

Abstract: Sex selection by flow cytometry/cell sorting involves the staining of spermatozoa with Hoechst 33342 in combination with the impact of a u.v. laser beam, two potentially mutagenic agents. A phenotypic and cytogenetic study of lymphocytes of piglets born after insemination with spermatozoa stained with Hoechst 33342 and from piglets obtained from stain-sorted spermatozoa was performed to evaluate the genotoxic effect of Hoechst 33342 staining and u.v. laser irradiation on the offspring. Lymphocytes from piglets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 39 publications
3
28
0
2
Order By: Relevance
“…After Hoechst-stained and UV-laser irradiated sperm nuclei were microinjected into hamster eggs, the n u m be r o f D N A b re a k s a n d t r i r a d i a l a n d quadriradial exchanges between the chromosomes that developed increased slightly. In a recent study, no genotoxic effects of sorting sperm with Hoechst 33342 were found in the cells of resulting pigs [41].…”
Section: Flow Cytometer Modification and X-and Y-sperm Separationmentioning
confidence: 90%
“…After Hoechst-stained and UV-laser irradiated sperm nuclei were microinjected into hamster eggs, the n u m be r o f D N A b re a k s a n d t r i r a d i a l a n d quadriradial exchanges between the chromosomes that developed increased slightly. In a recent study, no genotoxic effects of sorting sperm with Hoechst 33342 were found in the cells of resulting pigs [41].…”
Section: Flow Cytometer Modification and X-and Y-sperm Separationmentioning
confidence: 90%
“…Hoechst 33342, a type of blue- fluorescent dye, stains the condensed chromatin in apoptotic cells more brightly than normal chromatin, 38 while propidium iodide (PI), a red-fluorescent dye, only permeates into dead cells. Hoechst 33342, a type of blue- fluorescent dye, stains the condensed chromatin in apoptotic cells more brightly than normal chromatin, 38 while propidium iodide (PI), a red-fluorescent dye, only permeates into dead cells.…”
Section: Morphological Changes Against Qd Toxicity and Apoptosismentioning
confidence: 99%
“…Damage due to sexing sperm has also been cited as a reason for lower pregnancy rates (Seidel ; Parrilla et al . ). Despite the damage to the sexed sperm, which contributes to the lower fertility, the resulting offspring appear to be completely normal (Tubman et al .…”
Section: Discussionmentioning
confidence: 97%
“…No genotoxic effects of sexing the sperm with Hoechst 33342 have been found in cells in prior studies (Morrell & Dresser ; Parrilla et al . ), but staining with Hoechst 33342 and UV laser irradiation of the sperm during flow sorting tended to increase the incidence of chromosomal aberrations (Garner ). Damage due to sexing sperm has also been cited as a reason for lower pregnancy rates (Seidel ; Parrilla et al .…”
Section: Discussionmentioning
confidence: 99%